Clinical electrocardiographic studies of bifid T waves. Issue 2 (August 1984) - Watanabe, Y; Toda, H; Nishimura, M
Abstract : In 129 electrocardiograms from 129 patients showing bifid T waves as well as U waves the intervals from the beginning of the QRS complex to the two T wave apices (QaT1, QaT2), to the end of the T wave (QeT), and to the apex of the U wave (QaU) were measured. Eighty additional electrocardiograms from matched control subjects showing single peaked T waves were also studied. The precordial distribution of bifid T waves was assessed by calculating lead prevalence indices. This index progressively increased from 2.15 in the age range 20-29 years to 3.72 in the age range 60-69 years, and was significantly higher in patients with left ventricular hypertrophy and ischaemia (4.04) than in those with otherwise normal electrocardiograms (2.35). Thus older age and left ventricular pathology were accompanied by a more leftward location of bifid T waves. Exercise accentuated the bifid nature of the T wave in 12 of 18 patients with otherwise normal electrocardiograms, and diminished it in 11 of 19 cases with left ventricular hypertrophy and ischaemia. When 41 otherwise normal tracings showing bifid T waves were compared with those of 42 matched controls showing single peaked T waves, the QTc was longer and the eTaU interval shorter in the group with bifid T waves. Similarly, 40 patients with left ventricular hypertrophy and ischaemia showing bifid T waves had longer QTc and shorter eTaU intervals than 38 patients with the same diagnosis with single peaked T waves. These findings suggest that right precordial bifid T waves in younger patients with otherwise normal electrocardiograms probably result from delayed right ventricular repolarisation, whereas left precordial bifid T waves in older patients with left ventricular hypertrophy and ischaemia may indicate repolarisation delay in the ischaemic left ventricle.